Age-related differences in primary central nervous system lymphomas based on the SEER database - Lin, Tengjiao; Wang, Ke; Yang, Deyu; Li, Zhichao; Zheng, Chuangjie; Chen, Xinrong; Zhai, Linzhu (Frontiers in Medicine, 2025)
ObjectiveThe aim of this study was to compare prognostic factors and survival outcomes in patients with primary central nervous system lymphoma (PCNSL).MethodsThe Surveillance, Epidemiology, and End Results (SEER) database was queried for patients diagnosed with PCNSL between 2000 and 2019.ResultsBetween 2000 and 2019, a total of 5,812 patients were diagnosed with PCNSL, of whom 2,175 (37%) were ≤ 60 years old and 3,637 (63%) were >60 years old. The younger patients had a higher rate of being diagnosed with stage I–II, a higher rate of receiving chemotherapy and radiotherapy, a similar rate of receiving surgery, and a longer survival time. The most common histological subtype among PCNSL patients was diffuse large B-cell lymphoma (PCNS-DLBCL). Younger PCNS-DLBCL patients who received surgery and chemotherapy exhibited significantly improved overall survival (OS) and disease-specific mortality (DSM) and that African American patients were associated with poorer OS and DSM. Older patients receiving surgery, chemotherapy, and radiotherapy exhibited significantly improved OS and DSM, male and higher Ann Arbor stage were associated with poorer OS and DSM. We created a nomogram for PCNS-DLBCL to predict OS, with a C-index of 0.6749 in the younger cohort and 0.6676 in the older cohort. In the combined therapy analysis, chemotherapy combined with surgical resection had better OS and DSM in all patients.ConclusionsThe two age-stratified cohorts significantly differed in terms of OS and independent influences on OS and DSM. Our constructed nomogram exhibited high accuracy in predicting OS in PCNS-DLBCL patients.